Gasoline content regulation and compliance among US refineries - Ujjayant Chakravorty; Céline Nauges; Henry Thille (Center for Economic Studies and ifo Institute (CESifo), 2012)
The US refining industry is a leading producer of sulfur oxide and nitrogen oxide emissions. As a result of the Clean Air Act, it has been subject to a host of environmental regulations that prescribe the production processes firms can employ and limits their emissions based on the permits they hold. Refiners must also produce gasoline that varies in quality by location to meet local, state and federal air quality standards. Empirical evidence suggests that a much larger proportion of firms in the industry have been non-compliant with Clean Air Act statutes than in other industries. We study the link between gasoline content regulation and the compliance behavior of refineries. We find that in areas with more stringent gasoline regulation, there was increased compliance on the part of firms.
Keywords: Q53; Q58; L52; 330; Clean Air Act; compliance behavior; energy markets; product regulation; petroleum refining; environmental pollution; Erdölraffinerie; Luftverunreinigung; Benzin; Produktqualität; Regulierung; Luftreinhaltung; Normbefolgung; USA